Last Patents on Bubble Electrospinning - Liu, Guo-Liang; Zhang, Yu-Meng; Tian, Dan; Zhou, Bang-Ze; Lu, Zhen-Qian; Wang, Chun-Xia (Recent Patents on Nanotechnology, 2020)
Due to their unique properties, nanofibers have been widely used in various areas, for example, information industry, pharmaceutical application, environmental industry, textile and clothing, etc. Bubble electrospinning is one of the most important non-needle electrospinning methods for nanofiber fabrication. It usually uses polymer bubbles for the production of nanomaterials by using electrostatic force, flowing air or mechanical force to overcome the surface tension of bubbles. Bubble electrospinning mainly includes bubble electrospinning and blown bubble electrospinning. History of the development of bubble electrospinning is briefly introduced in this article, and the most promising patents on the technology are elucidated. The methods of bubble electrospinning are single bubble electrospinning, porous bubble electrospinning, blown bubble electrospinning, electrostatic-fieldassisted blown bubble spinning and others. These different bubble electrospinning methods are also discussed in this paper.
Keywords: industrial production